Harnessing Plastic Waste: The Utilization of the Ecobrick Method in Jatiwaringin Village, Mauk District, Tangerang Regency - Ahmad Adriansyah; Karim Maulana; Nurikah Nurikah (Probono and Community Service Journal, 2022)
of handling and managing waste by recycling is another dimension that helps in the utilization of waste. Plastic waste originating from household activities is a problem wherever there are settlements, especially densely populated settlements. A method is needed to be able to reduce the production of waste into new products in order to be able to reuse the waste that has been disposed of. Tangerang Regency is one of the densely populated areas that has problems with household waste. Ecobricks or environmentally friendly bricks are made by compressing plastic waste into bottles to a certain density, 1 bottle of 600ml drinking water can compress plastic waste up to 200gr. The basic principle of Ecobrick is to make the people of Jatiwaring village want to reduce the production of plastic waste and can make something of value. If every household turns their household plastic waste into Ecobrick, a lot of plastic waste will be reduced from the Final Processing Site (TPA). We involve the people of Jatiwaringin village to overcome the problem of the large amount of plastic waste production in Jatiwaringin Village, starting from providing an understanding of the importance of suppressing plastic waste production and providing training and assistance on how to make Ecobricks. The results of this study state that Ecobricks are an effective step to reduce household-level waste production, besides that the work made from Ecobricks also has the potential to increase the eco the economic value of household scale.